Struggles in "the Stronghold of World Imperialism": East German. Issue 2 (1st June 2019) - Johnson, Jason
Abstract : This article centers on the League of People's Friendship of the German Democratic Republic. The League, composed of a main organization in East Berlin and national partner societies scattered around the globe, served as a tool of nontraditional diplomacy for East Germany's ruling communist party across much of the Cold War. This article sketches out the activities of the League's partner organizations in the U.S.—the first analysis to do so—arguing first that given the variety of challenges and problems the League and its partner organizations faced, the limited success of these groups in the U.S. is, in the end, rather remarkable. Second, this essay argues that these organizations offer further evidence that East Germany was not exactly a puppet state.